The Effect of Guided Discovery Method and Learning Interest on Students' Understanding of Physics Concepts - Kaharuddin Arafah (Universitas Muhammadiyah Makassar, 2020)
This study aims to analyze differences in understanding of physics concepts between students taught using the guided discovery method with varied lectures, both overall, for high learning interest and for low learning interest. In addition to knowing the interaction between learning methods and learning interest in understanding students' physics concepts. To achieve this goal, an experimental study using a 2 x 2 factorial design was conducted. The population of the study was 193 students of class XI IPA of SMAN 18 Makassar in 2018/2019 Academic Year. The sample subjects of this study were taken through cluster sampling techniques, amounting to 64 people. Two classes as an experimental group were taught using the guided discovery method and two classes as a control class were taught with a varied lecture method. Data were analyzed using descriptive statistics and inferential satelistic two-way ANAVA at a significance level of 5%. The results of the descriptive analysis showed that the average score of understanding the physics concepts of the experimental group students was 18.57 with a standard deviation of 2.53. The average score of understanding the physics concepts of the control group students was 14.56 with a standard deviation of 2.86. The results of inferential analysis show that overall, there are differences in understanding of physical concepts between students taught using the guided discovery method and those taught with varied lectures. Further results, both for high learning interest and those with low learning interest, there are differences in understanding of physics concepts between students taught using the guided discovery method with varied lectures. Finally, the results obtained that there is no interaction between learning methods with interest in learning about understanding students' physics concepts.